You have the following function:
f(x) = x² + x - 12
In order to find the roots of the previous function, use the quadratic formula:
![f(x)=\frac{-b\pm\sqrt[]{b^(2)-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/ajdfq3chmlizgp1d0xsa070jcz60o6ken8.png)
take into account that the general for of a quadratic function is:
f(x) = ax² + bx + c
by comparing the previous function with the given function of the question you have:
a = 1, b = 1, c = -12
repalce these values into the quadratic formula:
![\begin{gathered} x=\frac{-1\pm\sqrt[]{1^(2)-4(1)(-12)}}{2(1)} \\ x\text{ =}\frac{-1\pm\sqrt[]{49}}{2} \\ x=(-1\pm7)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/42lv6yz1wawycqkie6k0umym8lnyn45r5r.png)
from the previous expressio for x, you obtain two solutions:
x = (-1-7)/2 = -8/2 = -4
x = (-1+7)/2 = 6/2 = 3
Hence, the roots of the given function are -4 and 3. And Scott is wrong